2021
DOI: 10.1590/1807-3107bor-2021.vol35.0132
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT evaluation of root canal preparation with rotary instrumentation on prototyped primary incisors

Abstract: This study aimed to evaluate the endodontic instrumentation outcomes with asymmetrical files compared to reciprocating and hand files (HFs) in 3D-printed prototypes of upper primary incisors using micro-computed tomography (micro-CT). For this purpose, 50 prototypes were randomly divided (n = 10) according to the instrumentation technique as follows: HFs, a reciprocating file (WaveOne ® Gold [WOG]), and three asymmetrical movement files: XP-Endo ® Shaper (XPS), XP-Endo ® Finisher (XPF), and XP Clean (XPC). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Regarding the sample included in the studies obtained ( Table 1 and Table 2 ), most of them analyzed an average of 30 teeth [ 10 , 11 ]. Highlighting Mohammadi, D [ 12 ], with a maximum of 80, and Moraes [ 13 ] with a minimum of 1. Regarding the variables analyzed, and considering the length of the files, the longest were those used by Gekelman [ 14 ], with a length 25 mm, and the shortest, 15 mm, used by Mohammadi [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the sample included in the studies obtained ( Table 1 and Table 2 ), most of them analyzed an average of 30 teeth [ 10 , 11 ]. Highlighting Mohammadi, D [ 12 ], with a maximum of 80, and Moraes [ 13 ] with a minimum of 1. Regarding the variables analyzed, and considering the length of the files, the longest were those used by Gekelman [ 14 ], with a length 25 mm, and the shortest, 15 mm, used by Mohammadi [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, regarding the irrigant used, sodium hypochlorite is the most used at different concentrations: 2.5% [ 10 ], 5.25% [ 11 ] or 1% [ 11 ], although other authors also use saline solution to eliminate bacteria [ 13 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The latter is a finishing single-file system that has been suggested as an effective and yet conservative approach in the instrumentation of primary teeth. 12 In addition, it has been also shown that full sequence rotary instruments dedicated to primary teeth (Kedo) result in less debris extrusion than non-dedicated systems. 30 In the present study, K-files and XPS instrumentation resulted in more hard tissue debris accumulation inside the root canal.…”
Section: Groupsmentioning
confidence: 99%
“…In general, most studies corroborate the results herein, in which rotary systems achieve similar or better results than manual files in terms of shaping ability and mechanical instrumentation time in primary molars. 4,6,12,24,[31][32][33][34][35] Canal transportation corresponds to the deviation observed after instrumentation, compared with the initial sound canal, being generally evaluated in mesial roots of permanent mandibular molars. 36 Mesial roots are interesting due to its complex canal morphology and because it closely matches the internal and external morphology of the primary mandibular second molar.…”
Section: Groupsmentioning
confidence: 99%
See 1 more Smart Citation